Accessing genitourinary medicine clinics: does it matter where you live?. Issue 3 (13th April 2011) - Stuart, Beth; Hinde, Andrew
Abstract : Objectives: To determine whether genitourinary medicine (GUM) clinics in England are located conveniently for potential users and to assess whether there are any regional variations in accessibility. Methods: A surface model was created in ArcGIS to estimate driving times to the nearest GUM clinic and to identify the proportion of the population living more than 30 minutes drive from their nearest clinic. Results: Overall, 3.0% of the population live further than 30 minutes from their nearest clinic. However, this average figure disguises considerable regional variation. While access in London and the South East was excellent, with less than 1% of the population living more than 30 minutes from the nearest clinic, in the South West and the East of England, these percentages rose to 7.7% and 9.2%, respectively. Conclusions: In some regions of England it is important to consider the physical barriers to clinic access, as inability or unwillingness to undertake a long journey to a GUM clinic may increase the workload in other clinical settings.